Fungal exposome, human health, and unmet needs: A 2022 update with special focus on allergy. Issue 11 (1st September 2022) - Vitte, Joana; Michel, Moïse; Malinovschi, Andrei; Caminati, Marco; Odebode, Adeyinka; Annesi‐Maesano, Isabella; Caimmi, Davide Paolo; Cassagne, Carole; Demoly, Pascal; Heffler, Enrico; Menu, Estelle; Nwaru, Bright I.; et al.
Abstract: Humans inhale, ingest, and touch thousands of fungi each day. The ubiquity and diversity of the fungal kingdom, reflected by its complex taxonomy, are in sharp contrast with our scarce knowledge about its distribution, pathogenic effects, and effective interventions at the environmental and individual levels. Here, we present an overview of salient features of fungi as permanent players of the human exposome and key determinants of human health, through the lens of fungal allergy and other fungal hypersensitivity reactions. Improved understanding of the fungal exposome sheds new light on the epidemiology of fungal‐related hypersensitivity diseases, their immunological substratum, the currently available methods, and biomarkers for environmental and medical fungi. Unmet needs are described and potential approaches are highlighted as perspectives.